Brace treatment for patients with scoliosis: State of the art - KURU ÇOLAK, TUĞBA (AOSIS, 2021)
Background: Physiotherapy, brace applications or surgery are the treatment options utilised to manage patients with scoliosis. Many different brace applications are used, and the success rates of orthoses vary. Objectives: Brace applications can have detrimental impacts on the patient leading to physical discomfort, psychological discomfort, and in some instance the use of braces may even be painful. Therefore, future developments in this field should be aimed at improving the success rate and reducing physical distress experienced by the patient while using brace applications. The purpose of this article is to provide recommendations with respect to the most appropriate bracing approach in general. Method: A narrative review of the scientific literature was carried out to substantiate the statements made in this article. Results: The most important braces provided for the treatment of patients with scoliosis and the treatment results that can be achieved are presented and discussed, taking into account the most recent systematic reviews. A wide range of success rates have been found for the different brace applications. Conclusion: Given that brace application may impact the patient leading to physical discomfort and psychological distress, good quality management in brace application for patients with scoliosis is needed to ensure the best possible outcome and the least stressful management. Clinical implications: Safety in brace application for patients with scoliosis needs improvement. The use of standardised and reliable computer aided design (CAD) libraries and appropriate patient information based on published guidelines is suggested.
Keywords: scoliosis; brace application; outcomes; rate of success; cosmesis; ADOLESCENT IDIOPATHIC SCOLIOSIS; CONSERVATIVE TREATMENT; BENDING BRACE; EFFICACY; CURVE; ORTHOSIS; CRITERIA; SUCCESS; GIRLS